Locus of Control and Academic Attributional Style as Predictors of Academic Procrastination Behavior in Sports Sciences - Ceyhun Alemdağ; Tuğba Mataracı (Atatürk University, 2024)
This research is conducted to examine the academic procrastination behaviors of students studying at the faculty of sports sciences through the locus of control and academic attributional styles. However, the relationship between gender, grade level, sports participation status, age and gender variables with dependent variable also includes the sub-objectives of the research. The universe of the research consists of undergraduate students who is received sports education in the 2021-2022 academic year. The sample of the research consist of 332 (124 female 208 male) university students studying at the faculty of sports sciences of Trabzon University. In order to obtain the data, the personal information form, the Rotter Internal-External Locus of Control Scale, the Academic Procrastination Scale and the Academic Loading Styles Scale is used by the researcher. T-test, Anova, Pearson Correlation test, Manova and regression test is used to expound the data. According to the result which is obtained from the research, the academic procrastination behavior of the students of the Faculty of Sport Sciences is at low level, their locus of control is external locus of control and their academic attributional styles are pessimistic. After all, as the belief in locus of control is increased and the academic attributional styles of the students become pessimistic, the academic procrastination behavior is increased. When the relationship of demographic variables with academic procrastination, locus of control and academic attributional styles is examined, it was seen that male students exhibited more academic procrastination behavior compared to female students. It has been concluded that academic procrastination behavior increases as the overall academic grade point average decreases, female students are more locus of external control than male students, students who remain passive in sports are more locus of external control than active participants and academic attributional styles becomes pessimistic as age progresses.